Advantages and Disadvantages of Virtual Reality in Science Learning Systems in the 21st Century: A Review - Khairul; Iwan Purnama; Arie Wahyu Prananta; Ruth Rize Paas Megahati.S; Risnawati Agustin (Jurnal Penelitian Pendidikan IPA, 2025)
The rapid development of information technology has brought human civilization into the 21st century, which requires mastery of 21st-century skills, such as critical, creative, collaborative, and communicative thinking. Virtual reality offers an immersive and interactive learning experience, allowing students to interact with virtual environments as if they were real, thus potentially increasing conceptual understanding and learning motivation. Virtual reality has advantages and disadvantages in science learning. Where the purpose of the study is to examine the advantages and disadvantages of virtual reality in science learning systems in the 21st century: a Review, namely collecting information from previous studies related to the Advantages and Disadvantages of Virtual Reality in Science Learning Systems in the 21st Century This review was conducted based on the review method. The results of this study explain that there are several advantages and disadvantages of using a science learning system that uses virtual reality, one of the results that explains the advantages of virtual reality is Immersive Learning so that students can see learning concepts more realistically and not only focus on books or material explanations; teachers and one of the disadvantages of virtual reality in science learning is that VR systems can be expensive to develop and maintain, making them less accessible to organizations, educational institutions with limited budgets.